2015
DOI: 10.4103/0974-1208.158615
|View full text |Cite
|
Sign up to set email alerts
|

Impact of different controlled ovarian stimulation protocols on the physical and psychological burdens in women undergoing in vitro fertilization/intra cytoplasmic sperm injection

Abstract: CONTEXT:Infertility treatment involves a considerable amount of physical and psychological burden which may impact the outcome.AIM:The objective was to understand the amount of physical and psychological burden in women undergoing their first in vitro fertilization (IVF)/intra cytoplasmic sperm injection (ICSI) cycles.SETTING AND DESIGN:Multi-center, prospective, parallel, observational study.MATERIALS AND METHODS:The study was conducted across 12 IVF centers in India. A total of 692 women undergoing controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Finally, nine trials were included, all of them in non-clinical populations. Four trials compared GnRH agonists and GnRH antagonists (3,(34)(35)(36), showing a better mood profile (less depressive symptoms) for those hormonal protocols including antagonists in one trial. Two trials compared protocols using either GnRH agonists or GnRH antagonists versus natural cycle protocols that did not use gonadotropin stimulation, reporting a better mood profile in those protocols without gonadotropin stimulation (32,33).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Finally, nine trials were included, all of them in non-clinical populations. Four trials compared GnRH agonists and GnRH antagonists (3,(34)(35)(36), showing a better mood profile (less depressive symptoms) for those hormonal protocols including antagonists in one trial. Two trials compared protocols using either GnRH agonists or GnRH antagonists versus natural cycle protocols that did not use gonadotropin stimulation, reporting a better mood profile in those protocols without gonadotropin stimulation (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…One study suggested that treatment with one GnRH agonist, buserelin, had a poorer mood profile than other GnRH agonist (goserelin) 1 week later but showed similar mood changes at the end of the trial (37). However, GnRH agonists did not seem to differ from GnRH antagonists in their associated occurrence of depressive symptoms, suggesting that neither protocol has a psychopathological effect on women undergoing fertility treatments (3,(34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations